Linearization of Composite Material Damage Model Results and Its Impact on the Subsequent Stress-Strain Analysis - Vlach, Jarmil; Doubrava, Radek; Růžek, Roman; Raška, Jan; Horňas, Jan; Kadlec, Martin (Polymers, 2022)
To solve problems in the field of mechanical engineering efficiently, individual numerical procedures must be developed, and solvers must be adapted. This study applies the results of a carbon-fibre reinforced polymer (CFRP) analysis along with the nonlinear finite element damage (FE) method to the translation of a linear solver. The analyzed tensile test sample is modelled using the ply-by-ply method. To describe the nonlinear post-damage behavior of the material, the Hashin model is used. To validate the transformation, an analysis and comparison of the damage results of the linearized and nonlinear model is carried out. Job linearization was performed by collecting elements into groups based on their level of damage and pairing them with unique material cards. Potentially suitable mathematical functions are tested for the grouping and consolidation of the elements. The results show that the agreement of some presented methods depends on the damage level. The influence of the selected statistical functions on the result is shown here. The optimal solution is demonstrated, and the most efficient method of linearization is presented. The main motivation behind this work is that the problem has not been discussed in the literature and that there is currently no commercial software translator that provides the transference of models between solvers.
Keywords: Hashin; linear solver; composite; damage simulation; non-linear solver; linearization